SDH5, a Gene Required for Flavination of Succinate Dehydrogenase, Is Mutated in Paraganglioma - Hao, Huai-Xiang; Khalimonchuk, Oleh; Schraders, Margit; Dephoure, Noah; Bayley, Jean-Pierre; Kunst, Henricus; Devilee, Peter; Cremers, Cor W.R.J; Schiffman, Joshua D; Bentz, Brandon G; Gygi, Steven P; Winge, Dennis R; et al. (Science (American Association for the Advancement of Science), 2009)
Mammalian mitochondria contain about 1100 proteins, nearly 300 of which are uncharacterized. Given the well-established role of mitochondrial defects in human disease, functional characterization of these proteins may shed new light on disease mechanisms. Starting with yeast as a model system, we investigated an uncharacterized but highly conserved mitochondrial protein (named here Sdh5). Both yeast and human Sdh5 interact with the catalytic subunit of the succinate dehydrogenase (SDH) complex, a component of both the electron transport chain and the tricarboxylic acid cycle. Sdh5 is required for SDH-dependent respiration and for Sdh1 flavination (incorporation of the flavin adenine dinucleotide cofactor). Germline loss-of-function mutations in the human SDH5 gene, located on chromosome 11q13.1, segregate with disease in a family with hereditary paraganglioma, a neuroendocrine tumor previously linked to mutations in genes encoding SDH subunits. Thus, a mitochondrial proteomics analysis in yeast has led to the discovery of a human tumor susceptibility gene.